Minimally invasive glaucoma surgery: current status and future prospects - Richter GM (Dove Medical Press, 2016)
Grace M Richter,1,2 Anne L Coleman11UCLA Stein Eye Institute, Department of Ophthalmology, University of California, Los Angeles, CA, USA; 2USC Eye Institute, Department of Ophthalmology, Keck School of Medicine of University of Southern California, Los Angeles, CA, USAAbstract: Minimally invasive glaucoma surgery aims to provide a medication-sparing, conjunctival-sparing, ab interno approach to intraocular pressure reduction for patients with mild-to-moderate glaucoma that is safer than traditional incisional glaucoma surgery. The current approaches include: increasing trabecular outflow (Trabectome, iStent, Hydrus stent, gonioscopy-assisted transluminal trabeculotomy, excimer laser trabeculotomy); suprachoroidal shunts (Cypass micro-stent); reducing aqueous production (endocyclophotocoagulation); and subconjunctival filtration (XEN gel stent). The data on each surgical procedure for each of these approaches are reviewed in this article, patient selection pearls learned to date are discussed, and expectations for the future are examined. Keywords: MIGS, microincisional glaucoma surgery, trabecular stent, Schlemm’s canal, suprachoroidal shunt, ab interno